2010
DOI: 10.1007/s00430-010-0160-3
|View full text |Cite
|
Sign up to set email alerts
|

The underlying mechanisms for the “isolated positivity for the hepatitis B surface antigen (HBsAg)” serological profile

Abstract: During HBV infection, four structural antigen/antibody systems are observed: hepatitis B surface antigen (HBsAg) and its antibody (anti-HBs); the pre-S antigens associated with HBsAg particles and their antibodies; the particulate nucleocapsid antigen (HBcAg) and anti-HBc; and an antigen structurally related to HBcAg, namely HBeAg and its antibody (anti-HBe). Through the examination of this antigen-antibodies system, hepatitis B infection is diagnosed and the course of the disorder may be observed. Isolated HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Recent immunosuppressive therapy including rituximab for a non-Hodgkin lymphoma was the most likely causal mechanism. Lower anti-HBc production has been reported in immunocompromised individuals [7]. Furthermore, during an active phase of replication, high levels of HB core antigen (HBcAg) are released in the bloodstream and can induce HBcAg and anti-HBc immune complex formation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent immunosuppressive therapy including rituximab for a non-Hodgkin lymphoma was the most likely causal mechanism. Lower anti-HBc production has been reported in immunocompromised individuals [7]. Furthermore, during an active phase of replication, high levels of HB core antigen (HBcAg) are released in the bloodstream and can induce HBcAg and anti-HBc immune complex formation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, host immune incompetence such as T cell anergy or defective HBcAg-specific B cell, inducing tolerance after the initial allergen encounter, may consequently result in the absence of anti-HBc antibody production. [40][41][42] In our study, we recruited a nationwide population in Taiwan and demonstrated that the universal HBV immunization program effectively reduced the HBV prevalence, and no geographic difference was found in the four regions in terms of HBsAg and anti-HBc seroprevalence rates in the postvaccination era. However, HBV infection…”
Section: Notementioning
confidence: 78%
“…Since none of the had received HBV vaccines shortly before blood sampling and all denied having autoimmune diseases, this phenomenon may also be potentially linked to HBV variants in the S region. Alternatively, host immune incompetence such as T cell anergy or defective HBcAg‐specific B cell, inducing tolerance after the initial allergen encounter, may consequently result in the absence of anti‐HBc antibody production 40–42 …”
Section: Discussionmentioning
confidence: 99%
“…At present, routine laboratory tests to detect HBV infection are mainly serological and molecular assays. In recent years, some rare serological patterns appeared more frequently, including coexistence of HBsAg and anti-HBs, isolate positivity for HBsAg, and ‘anti-HBc alone.’ 1 , 2 The serological profile for coexistence of HBsAg and anti-HBs was firstly reported by Arnold et al 3 , 4 , 5 , 6 , 7 , 8 However, the underlying mechanism and clinical implication of this serological pattern in chronic hepatitis B patients remains controversial. 9 , 10 Many reports have suggested that this coexistent serological pattern might increase the risk of HCC in chronic HBV infection.…”
Section: Introductionmentioning
confidence: 97%